Effect of red thyme oil (Thymus vulgaris L.) vapours on fungal decay, quality parameters and shelf-life of oranges during cold storage. (30th January 2021) - Pinto, L.; Cefola, M.; Bonifacio, M.A.; Cometa, S.; Bocchino, C.; Pace, B.; De Giglio, E.; Palumbo, M.; Sada, A.; Logrieco, A.F.; Baruzzi, F.
Highlights: Red thyme oil vapours showed a MIC of 50 µL/L against Penicillium spp. RTO vapours controlled fungal decay on oranges during cold storage. Polypropylene was the appropriate packaging film for RTO application. p-Cymene was the main compound in vapour phase. Main quality and sensory parameters were not affected by RTO treatment. Abstract: This work has been aimed at studying the effect of red thyme oil (RTO, Thymus vulgaris L.) on the shelf-life and Penicillium decay of oranges during cold storage. RTO vapours significantly reduced ( P  ≤ 0.05) the percentage of infected wounds, the external growth area and the production of spores in inoculated orange fruit stored for 12 days at 7 °C in a polypropylene film selected for its appropriate permeability. Among the RTO compounds, p-cymene and thymol were the most abundant in packed boxes at the end of cold storage. The RTO vapours did not affect the main quality parameters of the oranges, or the taste and odour of the juice. The results have shown that an active packaging, using RTO vapours, could be employed, by the citrus industry, to extend the shelf-life of oranges for fresh market use and juice processing.